2020
DOI: 10.1111/jocd.13523
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of botulinum toxin injection after corrective rhinoplasty for deviated nose and alar asymmetry

Abstract: Background Deviated noses and asymmetric nostrils can be corrected using corrective rhinoplasty. However, after proper correction, adjacent facial mimetic muscles can cause recurrence of asymmetry because of preoperative habits. Objectives We performed this study to investigate the effects on botulinum toxin on the prevention of recurrence of asymmetry after corrective rhinoplasty. Methods From January 2016 to December 2019, 60 patients underwent corrective rhinoplasty and 30 received botulinum toxin type A in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Lee et al 9 studied the effect of injecting botulinum toxin into the bilateral DSN and LLSAN muscles immediately after surgery in 30 patients with anthropometric analysis and subjective aesthetic grading on photographs, 1 month and 6 months post-operatively. They found that patients receiving BTX had less horizontal and vertical deviation compared to the control group without significant adverse events 9 .…”
Section: (D) Guideline For the Use Of Botulinum Toxin In Myomodulatio...mentioning
confidence: 99%
See 4 more Smart Citations
“…Lee et al 9 studied the effect of injecting botulinum toxin into the bilateral DSN and LLSAN muscles immediately after surgery in 30 patients with anthropometric analysis and subjective aesthetic grading on photographs, 1 month and 6 months post-operatively. They found that patients receiving BTX had less horizontal and vertical deviation compared to the control group without significant adverse events 9 .…”
Section: (D) Guideline For the Use Of Botulinum Toxin In Myomodulatio...mentioning
confidence: 99%
“…They found that patients receiving BTX had less horizontal and vertical deviation compared with the control group without significant adverse events. 9 On the other hand, Yu et al 35 shared their anecdotal experience in treating bunny lines and nasal radix with BTX injection into the transverse nasalis muscle 1 week before rhinoplasty to reduce nasal skin tension and to reduce incidence of implant displacement and extrusion.…”
Section: "Nasal Muscle Imbalance Theory"-senior Author (Ad)'s Theorymentioning
confidence: 99%
See 3 more Smart Citations